ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA KELAS X TKJ SMK SWASTA HARAPAN - Siti Syahroni Harahap; Rahmatika Elindra; Nunik Ardiana (JURNAL MathEdu (Mathematic Education Journal), 2021)
The aim of this study is to know students’ creative thinking based high, average and low academic abilities. The approach of the research used qualitative and interview and test were used in collecting the data, the informant which included mathematics teacher and 5 students (1 student had high academic ability, 2 students had average academic, and 2 students had low academic). The results of the research shows student who had high academic had the skills to think fluently, breadth, authenticity, and detail, student who had average academic had good thinking skills but have not fully mastered the steps in solving the questions and conclusions of the questions, and students who had low academic abilities tend to have less creative thinking skills that are not good because they are unable to understand problems, make steps - steps in solving questions, the ability to think from one's own thoughts and make detailed answers.